Socioemotional and behavioural adaptation of students with disabilities: the significance of teacher–student attachment-like relationships. Issue 4 (1st October 2016) - Granot, David
ABSTRACT: The present study explores the extent to which maternal attachment and teacher–student attachment-like relationships explain the socioemotional adaptation of students with disabilities. Participants consisted of 65 dyads of homeroom teachers and their students (from a middle-to-low-class area in Northern Israel) with learning disabilities (LD), attention deficit hyperactivity disorder (ADHD), and LD/ADHD-co-morbidity (mean age = 10.9). Students were assessed based on the maternal attachment security scale (ASS) and the appraisal of the teacher as a secure base scale. Homeroom teachers completed the student-teacher security scale. Third-party teachers reported on students' school adaptation. Results indicated that beyond the disability factor, secure teacher-student relationships reduced the students' externalising problem behaviours and improved student learning proficiencies that are considered to be affected by the adequacy of executive functioning. Additionally, maternal attachment reduced internalising problem behaviours. Implications for the protective role of teachers of students with disabilities and for research on teacher–student relationship quality are discussed.